Effects of geometric parameters of a staggered labyrinth seal on leakage flow - Chun, Ye Hwan; Ahn, Joon (Journal of mechanical science and technology, 2023)
Staggered labyrinth seals are used in gas turbines for cooling turbine blades. In this study, numerical analyses were performed to evaluate the discharge coefficients about the shape variables of staggered labyrinth seals. Four shape variables were considered: cavity width (CW), staggered height (GH), staggered width (GW), and staggered position (GP). Changes in the discharge coefficient with the shape variables were analyzed. Strategies were investigated to decrease the discharge coefficient of a staggered labyrinth seal. The discharge coefficient of the optimized staggered labyrinth seal was 37 % smaller than that of a straight labyrinth seal. We hypothesized that the size of the vena contracta and acceleration in the axial direction were related to the discharge coefficient. However, an association between only the GW was not observed. The wall shear stress was sensitive only to the GH and independent of the other shape parameters.